Diffusion of ICT in education and the role of collaboration: a study of EdNA - White, Gerald Kingswood (Curtin University, 2010)
This research explored the diffusion of information and communications technology (ICT) innovations in education through a case study of Education Network Australia (EdNA) spanning fourteen years since EdNA's establishment in 1995.The study began by developing a comprehensive and original chronological history of the establishment, development and management of EdNA, with a particular focus on the collaboration amongst stakeholders in all of these phases. Four research questions were developed for the study to address. Evidence from documentary analysis, interviews with stakeholders and personal recollections was triangulated in addressing those questions.From a theoretical point of view, in the absence of theory specific to diffusion of ICT innovations in education, the research used as a theoretical starting point the work of Rogers (2003) on diffusion of innovations more generally. The analysis and interpretation of the literature related to Rogers’ theory highlighted that the likelihood of success of an innovation appears to be linked to its antecedents and pattern of its take up.An additional dimension of the theoretical framework of this study concerned the concept of collaboration amongst stakeholders – demonstrably a key concept in relation to EdNA, but one which has been very poorly defined in the literature. This study therefore developed a clear definition of collaboration in education for application to large scale projects such as EdNA, distilling the definition and characteristics of collaboration from previous work by Education.au Limited (2004) and Clark (2008).The above led to the theoretical proposition that the successful diffusion of an ICT innovation in education can be judged by its antecedents, its rate of population take up and the strength of collaboration associated with it. This theory was tested through a detailed analysis, using evidence from the EdNA case study.The findings of the study were that the new theory provided a robust basis for analysis of the diffusion of EdNA and the role of collaboration in that diffusion. Specifically, collaboration was found to be strong at high levels of influence (senior officials) in the establishment phases of the development of EdNA with leadership from the Commonwealth and a commitment to the initiative by State education and training Ministers and their senior staffs. The indicators of the likelihood of success were in place within five years after which time the national bodies sought a wider education technology agenda. The national initiative then operated by cooperation (Himmelmann, 1993) for a short period before moving to coordination by Education.au as the managing body in consultation with the Commonwealth and the States. During the coordination period innovation with EdNA services and new social technologies deployed on EdNA were strong and led to the emergence of online collaboration among users.The shift from national collaboration at a high level of influence in establishing the EdNA initiative to online collaboration among users as a result of innovation supports the proposal that collaboration in education is the process of co-creating knowledge while sharing physical or virtual space. However, this research did not support the view that the role of collaboration, beyond the establishment of the initiative, had a positive effect on the diffusion of ICT innovations in education because intensive collaboration is very demanding in terms of time and resources.This study addressed major theoretical and analytical gaps in the literature on diffusion of large-scale, national ICT innovations in education. It provides a sound basis for future research and practice.